A rare case of endometriosis to clear cell ovarian carcinoma: a case report - T., Anaswara; Venugopalan, Prasanna; Nair, Vidhu V.; George, Alfy Ann; Praseeda, I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Clear cell carcinoma of ovary is a rare tumour with a very low incidence in pregnancy. It is attributed to develop from an existing background of endometriosis. There are very few case reports of the above combination tumours in pregnancy. It is a very aggressive tumour with a worse prognosis and low survival rate because of its peculiar chemo resistant nature. Early detection and effective treatment are the best approach. The treatment options for advanced stages are still under research.